Coplanar stripline‐fed compact UWB antenna. Issue 17 (1st August 2014) - Roshna, T.K.; Deepak, U.; Sajitha, V.R.; Mohanan, P.
Abstract : A novel compact coplanar stripline (CPS)‐fed antenna for ultra‐wideband (UWB) application is investigated. The proposed antenna consists of a staircase‐shaped radiator together with a shorted strip. The prototype is designed on a substrate of dielectric constant 4.4, with an overall size of 25 × 7 × 1.6 mm 3 . The antenna offers a 2:1 voltage standing wave ratio (VSWR) bandwidth from 3.1 to 11.4 GHz, with an average gain of 3 dBi and average radiation efficiency of 75% throughout the band. The measured group delay and transmission characteristics show that the proposed antenna is a good candidate for UWB communication systems.